2015
DOI: 10.1177/0884533614567716
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Protein Intake Is Associated With Increased Mortality in 630 Patients With Cirrhosis Awaiting Liver Transplantation

Abstract: In this large cohort of liver transplant waitlisted patients, very low protein intake was prevalent and independently associated with malnutrition and mortality. Unlike many other prognostic factors, protein intake is potentially modifiable. Prospective studies are warranted to evaluate the effect of targeted protein repletion on clinically relevant outcomes such as muscle mass, muscle function, immune function, and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
2
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 43 publications
5
41
2
9
Order By: Relevance
“…However, its accuracy in predicting other health outcomes in cirrhosis remains unclear 3,13,[29][30][31][32][33] . The current study supports the conclusion that the SGA has limited capacity to identify sarcopenia.…”
Section: Use Of the Subjective Global Assessment (Sga) In Cirrhosismentioning
confidence: 99%
“…However, its accuracy in predicting other health outcomes in cirrhosis remains unclear 3,13,[29][30][31][32][33] . The current study supports the conclusion that the SGA has limited capacity to identify sarcopenia.…”
Section: Use Of the Subjective Global Assessment (Sga) In Cirrhosismentioning
confidence: 99%
“…Sarcopenia was firstly described as a physiologic process occurring with ageing characterized by a reduction in muscle mass and function; in cirrhosis the reduction in muscle protein synthesis and the increased protein catabolism lead to sarcopenia. Many studies have shown that sarcopenia deeply affects the prognosis of cirrhotic patients …”
Section: Introductionmentioning
confidence: 99%
“…The latter finding is in accordance with previously reported data[17] and with findings from our local data in 630 liver transplant listed patients with cirrhosis, where we demonstrated that only 24% of patients met protein intake targets. [18]…”
Section: Discussionmentioning
confidence: 99%
“…Second, there was no healthy control group included in our study. Third, as it has previously been evaluated,[293031] and as it would have extended the survey duration considerably, we did not collect detailed data on anthropometrics or calorie and protein intake in this population. Consequently, it was not possible to directly examine the relationship between our identified barriers, nutritional status, or quantitative macronutrient intake.…”
Section: Discussionmentioning
confidence: 99%